Asymmetry in the Expression of Bilateral Morphs as an Indicator Showing the Character of Interrelations Between Fleas and the Plague Pathogen - A. Ya. Nikitin; V. M. Korzun; E. G. Tokmakova; L. P. Bazanova (Проблемы особо опасных инфекций, 2008)
The level of fluctuating asymmetry (FA) of bilateral signs in fleas was shown to reflect a certain character of their interrelations with Yersinia pestis. Flea imagoes that had bacterial aggregations in their proventriculi demonstrated greater signs of FA chaetotaxy. Besides, in the experiments with groups of fleas originally differing in the intensity of FA expression, increased vector capacity was characteristic of individual fleas with higher levels of this index or those caught in the areas of the natural foci where epizootics had been registered. These peculiar interrelations manifested themselves both at intra- and inter-population levels in several species of Siphonaptera order, as well as in the imago hybrids originating from crosses between C.tesquorum altaicus and C.t.sungaris.